Mediatization of Religious Communication in Digital Space: Content Analysis of Religious Messages of The Jemaat Ahmadiyah Indonesia in Digital Space - Rusmulyadi; Cholidah, Lida Imelda (Fakultas Dakwah UIN Saizu Purwokerto, 2025)
This study explores the religious messages of the Jemaat Ahmadiyah Indonesia (JAI) as a practice of religious mediatization in digital space. Using the qualitative content analysis method and hermeneutic framework, this study analyzes religious messages on the official website of the JAI (Ahmadiyah.id). The text was selected based on purposive sampling criteria. The selection criteria for the sample text focus on writings that diverge from the beliefs held by mainstream Islamic groups. Specifically, the text addresses the Ahmadiyya movement, outlining the teachings regarding the prophethood of Mirza Ghulam Ahmad and the roles of Prophet Isa and Imam Mahdi, alongside discussions on the concept of Jihad. This study found that the internet is a bridging communication that connects with the public, a medium for disseminating religious messages (proselytizing), and an advocacy and self-defense channel to fight for justice and social equality. In this process, JAI frames messages to be widely accepted by the public. This approach is essential due to the fact that, as a minority religious group, JAI continues to face rejection and limitations. This research also revealed that the online environment contributes to mediating religious messages. The internet serves as both a source and a distributor of these religious messages. In other words, the internet has evolved into a medium for transmitting and communicating religious content.